Is competition good or bad for the price, quantity, and quality of bank lending? - Japan Huynh (PLoS ONE, 2023)
This paper extends the existing literature by examining an important channel through which bank competition could drive the real economy by comprehensively influencing bank lending in three components-price, volume, and quality. For the measurement of bank competition, we build a series of different structural (concentration indicators) and non-structural (Lerner, Boone, and Panzar-Rose H-statistic indexes) measures, given that the reliance on solely one individual measure could lead to a misleading conclusion. Through a sample of commercial banks during 2007-2021 in a single Vietnamese banking market, we find a decline in bank loan growth and a rise in credit risk under the pressure of high competition. With respect to the association between bank competition and the price of credit, our empirical evidence is mixed based on different measures to analyze the banking market structure. Our findings support the view that greater competition results in a less proliferated banking sector with riskier assets. We also confirm that these findings are robust to additional tests, including employing alternative measures of bank lending dimensions and market structure, removing the periods of the financial crisis and the COVID-19 pandemic, and changing the empirical estimation technique. In addition, our deeper analysis reveals that the adverse impact of bank competition on lending, shown by reduced credit supply and increased credit risk, is less pronounced for banks with a higher degree of income diversification. This result suggests that bank diversification may protect the quantity and quality of bank lending from the detrimental competition effect.